Settler sayings - Kalman, Bobbie (Crabtree Pub. Co. New York, 1994)
this book explores the words, phrases, and sayings that were used by settlers in North America and looks at their modern meanings.
910L
Keywords: Pioneers -- North America -- Quotations, maxims, etc. -- Juvenile Literature